Diaries of Field Marshal Mohammad Ayub Khan : 1966-1972 - Edited and Annotated by Baxter, Craig (Karachi, Pakistan Oxford University Press, 2007)
Field Marshal Ayub Khan kept his diary from September 1966 to October 1972, a very active period in Pakistan's history. Ayub's diary presents his views and interpretations of the events of the period for which it was kept. This title offers a means to understand the views of Ayub. It is intended for those studying the period.
Include Illustration, Note and Index
Keywords: Presidents -- Ayub Khan, Mohammad, 1907-1974 -- Pakistan